The Role of the Platform Economy in Transforming Automotive Suppliers: A Case Study of the Northern Black Forest - Bernhard Kölmel; Rebecca Bulander; Lukas Waidelich; Luc Schmerber; Luca Fischer; Abderrahim Moussaref (Platforms)
The European automotive industry, particularly in Germany, faces a significant crisis, heavily impacting suppliers reliant on OEMs. To enhance resilience, participation in the platform economy has been proposed as a solution. This study employs a qualitative research approach by conducting 18 expert interviews with automotive companies in the Northern Black Forest region to assess their awareness, perceived potential, and support needs regarding platform-based business models. The findings reveal diverse perspectives: smaller firms perceive higher risks, while larger companies recognize potential but struggle with limited expertise. The results highlight the novelty of the platform economy within the supplier industry and the need for increased awareness, strategic guidance, and tailored support measures. This study provides original insights into regional supplier engagement with platform ecosystems, contributing to the limited research on this topic and offering a foundation for future industry adaptation strategies.